Pelatihan Konseling Berbasis Psikososial Bagi Relawan Anak Jalanan di Kota Bandung - Ecep Supriatna; Rahmat Syarif Hidayat; Eunkeu Agiati; Rini Hartini Rinda Andayani (Jurnal Pengabdian Tri Bhakti, 2024)
The living conditions of street children in Bandung City are an urgent social issue, considering that they often live under pressure without adequate access to education, health, and a safe environment. This situation makes them vulnerable to psychosocial problems, such as emotional disorders, behavioral problems, and trauma. Community volunteers have a strategic role in supporting the mental well-being of street children, although they are often limited in knowledge and skills related to psychosocial-based counseling interventions to overcome these challenges, the Indonesian Educational Psychology Association (APPI) for the West Java region, Psychology lecturers at Bhayangkara Jaya University, and the Bandung Social Welfare Polytechnic (Poltekesos), collaborated to implement a psychosocial-based counseling training and mentoring program for street child community volunteers. This program aims to increase the capacity of volunteers in providing psychosocial intervention-based counseling services. These activities include theoretical training, counseling simulations, and case studies by experts. Volunteers are equipped with basic knowledge of psychosocial approaches, counseling skills, and emotional management to support the welfare of street children. The results of the activities showed an increase in the volunteers' understanding and skills related to psychosocial counseling. Volunteers are able to provide more effective support, so that it can have an impact on improving the emotional well-being of street children. The program also strengthens the community volunteer network and becomes a sustainable intervention model. The implication is the synergy between academics and volunteers, thus strengthening efforts in creating an inclusive environment, so that street children have hope for a better future.